Implementation of International Human Rights Obligations in Nigeria: Civil Society Perspective - Emelonye, Uchenna (Advances in Social Sciences Research Journal, 2021)
Civil society organizations are key actors in the promotion and protection of human rights in Nigeria and have participated in all the Universal Periodic Review (UPR) circles of the Government of Nigeria. The UPR is a first of its kind innovation adopted in 2006 by the Human Rights Council to complement the works of treaty bodies and involves the review on a periodic basis, the human rights records of all Member States of the United Nations. As a peer review process comprising three distinct stages and involving three major sources of information, this article exclusively ex-rays the UPR civil society report on the implementation of Nigeria’s international human rights obligations. As one of the three sources of information relied upon by the Human Rights Council in the Universal Periodic Review of the human rights record of the Government of Nigeria, this article, while focusing on the civil society information submitted to the Human Rights Council pursuant to the United Nations General Assembly Resolution 60/251 concludes that despite advances in the promotion and protection of human rights claimed in its national report to be made in the implementation of international human rights obligations, there are still, from civil society lens, plethora of issues and gaps in the implementation of Nigeria’s international human rights obligations.